The politics of children's services reform : re-examining two decades of policy change - Purcell, Carl (Policy Press, 2020)
Drawing on access to prominent policy makers, Purcell examines the origins and impact of children's services reform under recent Labour and Conservative-led governments, including Labour's Every Child Matters programme and the Munro Review. He also reassesses the impact of high-profile child abuse cases, including Victoria Climbié and Baby P.